La razonabilidad de la declaratoria de inconstitucionalidad de la preferencia materna en casos de tenencia: Estudio de la Sentencia de la Corte Constitucional No. 28-15-IN - Gordón Vega, Katherine Samantha (2024)
This research adopts a qualitative approach that allows for a deeper analysis of the problem raised. Through the documentary review, the imperative need to examine Ruling 28-15- IN/21 issued by the Constitutional Court of Ecuador is revealed, focusing on an exhaustive analysis of various legal institutions, especially with regard to tenancy in the Ecuadorian context. The declaration of unconstitutionality alters the regulations of a figure that has had great importance in the family courts, particularly after matters related to the maintenance regime. This work is based on the doctrinal analysis of constitutional principles such as the best interests of the child, co-parenting, parental co-responsibility and sensitive aspects that must be considered in a patriarchal system, such as vicarious violence and the gender role assigned to women. However, the main focus is on the study and determination of the criteria and arguments of the judges of the Court. In addition, the reasonableness and motivation of the sentence is examined through the analysis of constitutional principles and the need to ensure the rights of children and adolescents in a framework of protection and rights.